Avaliação da reação em cadeia da Polimerase (PCR) em PBMC e lavado broncoalveolar para o diagnóstico da anemia infecciosa eqüina. - Elizangela Maira dos Santos (2006)
Equine Infectious Anemia Virus (EIAV) is a retrovirus that causes Equine Infectious Anemia, a disease that strikes animals from family Eqüidae. In the present study, PCR (polymerase chain reaction) techniques were evaluated as a confirmation test for ELISA serologic tests and IDGA. Samples of bronchoalveolar lavage fluid (BALF), peripheral blood mononuclear cells (PBMCs) and serum from IDGA-positive equids that were slaughtered in cold storage plants were analyzed. DNA samples from BALF and PBMCs were submitted to amplification by -Actin PCR, gag nPCR and gp90 PCR. -Actin PCR was found to be an efficient quality control resource for genomic DNA submitted to the other techniques. gp90 PCR was not able to amplify the Brazilian samples of DNA from BALF and PBMCs from AIE-positive animals. gag nPCR was efficient in the amplification of viral sequences in PBMCs samples and can be utilized as a confirmation diagnostic test for serologic techniques.